A longitudinal, multi-parametric functional MRI study to determine age-related changes in the rodent brain - Andrew Crofts; Melissa Trotman-Lucas; Justyna Janus; Michael Kelly; Claire L. Gibson (NeuroImage, 2020)
As the population ages, the incidence of age-related neurological diseases and cognitive decline increases. To further understand disease-related changes in brain function it is advantageous to examine brain activity changes in healthy aging rodent models to permit mechanistic investigation. Here, we examine the suitability, in rodents, of using a novel, minimally invasive anaesthesia protocol in combination with a functional MRI protocol to assess alterations in neuronal activity due to physiological aging. 11 Wistar Han female rats were studied at 7, 9, 12, 15 and 18 months of age. Under an intravenous infusion of propofol, animals underwent functional magnetic resonance imaging (fMRI) and functional magnetic resonance spectroscopy (fMRS) with forepaw stimulation to quantify neurotransmitter activity, and resting cerebral blood flow (CBF) quantification using arterial spin labelling (ASL) to study changes in neurovascular coupling over time. Animals showed a significant decrease in size of the active region with age (P ​< ​0.05). fMRS results showed a significant decrease in glutamate change with stimulation (ΔGlu) with age (P ​< ​0.05), and ΔGlu became negative from 12 months onwards. Global CBF remained constant for the duration of the study. This study shows age related changes in the blood oxygen level dependent (BOLD) response in rodents that correlate with those seen in humans. The results also suggest that a reduction in synaptic glutamate turnover with age may underlie the reduction in the BOLD response, while CBF is preserved.